Relationship of Lipid Profiles to Stroke Patients: Systematic Review - Nurhayati Puspita, Uci; Septianingrum, Yurike; Wijayanti, Lono; Soleha, Umdatus (Chakra Brahmanda Lentera Institute, 2024)
Background: Stroke is the second leading cause of death and a major contributor to disability worldwide, with the highest prevalence in developing countries. Ischemic stroke is the most common type, caused by blood flow obstruction due to blood clots or fatty plaque accumulation (atherosclerosis). Hemorrhagic stroke, on the other hand, occurs due to blood vessel rupture and bleeding in the brain. This systematic review aims to explore the relationship between lipid profiles and stroke incidence. Methods: This study employed a systematic review approach using the PRISMA methodology. Articles were sourced from databases including Google Scholar, PubMed, ScienceDirect, and Cochrane Library, focusing on publications from 2019 to 2024. Keywords used for the search included